IMPLEMENTASI PROGRAM BANTUAN PANGAN NON TUNAI (BPNT) DINAS SOSIAL KOTA PEKANBARU DALAM MENANGGULANGI KEMISKINAN DI KELURAHAN MAHARATU KECAMATAN MARPOYAN DAMAI - Mulia Usna; Titi Maemunaty; Widiastuti Widiastuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The formulation of the problem in this study is how the implementation of the non-cash food aid program (BPNT) of the Pekanbaru city social service in tackling poverty in Maharatu Sub-District, Marpoyan Damai District and what are the benefits. The purpose of this study was to determine the implementation of the non-cash food aid program (BPNT) of the Pekanbaru city social service in tackling poverty in Maharatu Sub-District, Marpoyan Damai Sub-district and what the benefits were. This type of research is descriptive with a qualitative approach. The research subjects were 6 people, data collection techniques used observation, interviews and documentation. The results of the analysis carried out can be concluded the implementation of the non-cash food assistance program (BPNT), namely the implementation mechanism, control and inhibiting factors.Key Words: Implementation, Program, BPNT, Poverty